2010
DOI: 10.3389/fnins.2010.00192
|View full text |Cite
|
Sign up to set email alerts
|

A New Strategy for Antidepressant Prescription

Abstract: From our research and literature search we propose an understanding of the mechanism of action of antidepressants treatments (ADTs) that should lead to increase efficacy and tolerance. We understand that ADTs promote synaptic plasticity and neurogenesis. This promotion is linked with stimulation of dopaminergic receptors. Previous evidence shows that all ADTs (chemical, electroconvulsive therapy, repetitive transcranial magnetic stimulation, sleep deprivation) increase at least one monoamine neurotransmitter s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 124 publications
2
29
0
2
Order By: Relevance
“…Dopamine signaling is thought to affect consciousness by modulating cortico-basal ganglia-thalamic loops, with a central end mechanism being the impact upon glutamate-GABA processes in frontal cortical and temporal lobe regions (131). Several authors have suggested that dopamine system activation by ECT contributes to reduced depressive and anxious mood and increased positive mood, motivation, concentration, and attention, in line with the general effects of dopamine (133, 134). Within this scenario, frontotemporal effects of HPA axis activation may be closely associated with the dopamine system effects, as indicated for example by the role of glucocorticoid receptors in increasing PFC dopamine efflux following acute stress (135).…”
Section: Discussionmentioning
confidence: 92%
“…Dopamine signaling is thought to affect consciousness by modulating cortico-basal ganglia-thalamic loops, with a central end mechanism being the impact upon glutamate-GABA processes in frontal cortical and temporal lobe regions (131). Several authors have suggested that dopamine system activation by ECT contributes to reduced depressive and anxious mood and increased positive mood, motivation, concentration, and attention, in line with the general effects of dopamine (133, 134). Within this scenario, frontotemporal effects of HPA axis activation may be closely associated with the dopamine system effects, as indicated for example by the role of glucocorticoid receptors in increasing PFC dopamine efflux following acute stress (135).…”
Section: Discussionmentioning
confidence: 92%
“…It offered a novel perspective on etiology of MDD, but one that fit with the existing “scaffolding”: the concept of MDD as a limbic disorder marked by hippocampus maladaptations. The hypothesis also helped to explain the delay of several weeks between the initiation of antidepressant treatment and onset of their effects (Lavergne and Jay, 2010), since the maturation of the hippocampal progenitors into mature DG granule neurons and their incorporation into circuitry also takes about 3–4 weeks (Encinas et al, 2006; Kee et al, 2007; Kempermann et al, 2004). The tractability of the hypothesis, along with the rapid rate of discovery about neural stem cells, stages of neurogenesis, and novel ways to track, label and manipulate adult-generated neurons (e.g.…”
Section: The Neurogenesis Hypothesis Of Depression: An Overviewmentioning
confidence: 99%
“…This work by Cameron’s group also clarifies how the first postulate should be stated in the future: reduced neurogenesis may result in increased-depressive like behavior when the individual is stressed. However, since the neurobiology of depression relies on many different aspects of brain functioning and involves many proposed cellular and molecular mechanisms including changes in neurotrophic factors, synaptic plasticity, and even cell proliferation and survival outside of hippocampus (Castro et al, 2010; Krishnan and Nestler, 2008; Lavergne and Jay, 2010), it is unlikely that the adult hippocampal neurogenesis would influence them all. Similarly, antidepressants modulate a wide spectrum of brain functions and processes besides adult neurogenesis (Berton et al, 2006).…”
Section: New Scaffolding Needed To Keep Up With Constructionmentioning
confidence: 99%
“…Depression is a psychiatric disorder that presents as a reduction in self-confidence and a lack of confidence in the world and the future (1). Its core symptoms involve a depressed mood, anhedonia, irritability, difficulties in concentrating and abnormalities in appetite and sleep (2).…”
Section: Introductionmentioning
confidence: 99%